Thermal unfolding of small proteins with SH3 domain folding pattern. - Knapp, S; Mattson, P; Christova, P; Berndt, K; Karshikoff, A; Vihinen, M; Smith, C; Ladenstein, R (1998)
The thermal unfolding of three SH3 domains of the Tec family of tyrosine kinases was studied by differential scanning calorimetry and CD spectroscopy. The unfolding transition of the three protein domains in the acidic pH region can be described as a reversible two-state process. For all three SH3 domains maximum stability was observed in the pH region 4.5 < pH < 7.0 where these domains unfold at temperatures of 353K (Btk), 342K (Itk), and 344K (Tec). At these temperatures an enthalpy change of 196 kJ/mol, 178 kJ/mol, and 169 kJ/mol was measured for Btk-, Itk-, and Tec-SH3 domains, respectively. The determined changes in heat capacity between the native and the denatured state are in an usual range expected for small proteins. Our analysis revealed that all SH3 domains studied are only weakly stabilized and have free energies of unfolding which do not exceed 12-16 kJ/mol but show quite high melting temperatures. Comparing unfolding free energies measured for eukaryotic SH3 domains with those of the topologically identical Sso7d protein from the hyperthermophile Sulfolobus solfataricus, the increased melting temperature of the thermostable protein is due to a broadening as well as a significant lifting of its stability curve. However, at their physiological temperatures, 310K for mesophilic SH3 domains and 350K for Sso7d, eukaryotic SH3 domains and Sso7d show very similar stabilities.